Mixed odontogenic tumors in four young dogs: ameloblastic fibroma and ameloblastic fibro-odontoma. (January 2019) - Huang, Patrick; Bell, Cynthia; Wallace, Vanessa; Murphy, Brian G.
Ameloblastic fibroma (AF) and ameloblastic fibro-odontoma (AFO) are mixed odontogenic tumors (odontogenic tumors with induction) that are reported only rarely in dogs. These tumors are histologically complex and, to a degree, recapitulate the early stages of tooth development, comprising 2 types of tissue: neoplastic odontogenic epithelium, and induced ectomesenchyme (dental pulp). AFOs are distinguished from AFs by the additional presence of hard dental matrices such as dentin. Herein, we describe the key diagnostic features of AF and AFO in 4 young dogs.